2012
DOI: 10.1007/s00221-012-3283-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen and hyperbaric air treatment result in comparable neuronal death reduction and improved behavioral outcome after transient forebrain ischemia in the gerbil

Abstract: Anoxic brain injury resulting from cardiac arrest is responsible for approximately two-thirds of deaths. Recent evidence suggests that increased oxygen delivered to the brain after cardiac arrest may be an important factor in preventing neuronal damage, resulting in an interest in hyperbaric oxygen (HBO) therapy. Interestingly, increased oxygen supply may be also reached by application of normobaric oxygen (NBO) or hyperbaric air (HBA). However, previous research also showed that the beneficial effect of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 71 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Among susceptible brain regions, the hippocampus is known as the most vulnerable region to cerebral ischemia, and extensive neuronal death occurs in this region [1][2][3][4]. In the hippocampus, pyramidal neurons of the CA1 region undergo neuronal death/ degeneration some days after the initial ischemic insult, which is referred to as ''delayed neuronal death'' [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among susceptible brain regions, the hippocampus is known as the most vulnerable region to cerebral ischemia, and extensive neuronal death occurs in this region [1][2][3][4]. In the hippocampus, pyramidal neurons of the CA1 region undergo neuronal death/ degeneration some days after the initial ischemic insult, which is referred to as ''delayed neuronal death'' [5].…”
Section: Introductionmentioning
confidence: 99%
“…During studies in which HBO was administered after hypoxic‐ischemic brain injury, Yin showed that HBO reduced apoptosis . Malek confirmed these positive effects of HBO and also found that hyperbaric air when given within 1–6 h after transient forebrain ischemia was also beneficial. Other studies have demonstrated that HBO can attenuate spinal cord injury, possibly through stimulation of the production of glial cell line‐derived neurotrophic factor (GDNF), vascular endothelial growth factor (VEGF) and interleukin (IL)‐10.…”
Section: Introductionmentioning
confidence: 66%
“…The fixed factors in the analyses may include CONC, the concentration of glucose (5 mmol/L vs 55 mmol/L), ANOXIA, whether the nerve is continuously oxygenated (0) or subject to intermittent anoxia (1), as well as CYCLE which is an index of the time during the experiment from which the data is taken (1)(2)(3)(4)(5). In the anoxia experiments CYCLE is the number of anoxic periods preceding the time from which the measurements are taken.…”
Section: Statisticsmentioning
confidence: 99%
“…We agree with them that hyperbaric oxygen may represent a potentially important therapeutic option for post-arrest encephalopathy as well as other forms of brain injury. We also agree that animal studies of global brain ischemia suggest that hyperbaric oxygen may be beneficial with regard to neurologic outcome [2,3], although not all preclinical studies concur [4]. However, we did not include hyperbaric oxygen in our review on cerebral edema after cardiac arrest for several reasons.…”
Section: Dear Editormentioning
confidence: 99%